Taymāʾ I: archaeological exploration, palaeoenvironment, cultural contacts - Bagg, Ariel M. (Taymā. Multidisciplinary series on the results of the Saudi-German Archaeological Project, 2018)
This is the first of a series of books reporting on a Saudi-German archaeological project at at Taymāʾ: the current archaeological exploration of the oasis is contextualised with previous and ongoing research within the region, while offering a first overview of the settlement history of the site, possibly starting more than 6000 years ago